Comparative Study on Macroscopic Anatomy of Human Placenta in Term and Post Term Pregnancy (Central Asian Journal of Medical Sciences, 2020)
Objectives: We aimed to compare the macroscopic anatomy of human placenta in term and post-term pregnancy. Methods: This maternity hospital-based comparative study was carried out in Mongolia, in the year 2017-2018. For study purposes, placentae were collected from 1061 women between 17-44 years of age with live birth only. Term: 38 weeks to 40 weeks gestational period, and post-term: beyond 41 weeks gestational period. The macroscopic features of the placentae were measured as a standard protocol that is approved Department of Anatomy, Mongolian National University of Medical Sciences. Results: A total of rounded shapes was found in 72% of cases and oval in 26.3% cases, irregular shape in 1.7% cases of the three shape groups. The width and the weight of the placenta (t = 7.20, t = 13.27 respectively) were compared between groups term and post-term found to be significant (p < 0.001). Conclusions: We conclude that irrespective of term or post-term placentae, most of the placentae were round in shape. The averages of placental morphometric parameters of both of term or post-term placentae are in the normal limit. This study concludes that as the gestational period increases length, width, thickness, and weight of placenta increases in different.